Different mixtures of substrates with composted sewage sludge enriched and commercial substrate to quaresmeira - Lobo, Thomaz Figueiredo [UNESP]; Oliveira, Fernando Carvalho; Morgado, Bruna Tavares; Siqueira, Marcos Vinicius Bohrer Monteiro (Fronteiras: Journal of Social, Technological and Environmental Science, 2018)
Tibouchina granulosa (Quaresmeira) is used in reforestation projects due to its rapid growth. To ensure best results, viable alternatives, such as the sewage sludge, have been searched, since it offers quality to the seedlings and also contributes to the environment for being a reused substance. We evaluate the effects of the substrate with sewage sludge. In the experimental design, 5 treatments were used with 4 repetitions. The irrigation was performed 3 times a day for a period of 2.5 minutes. The best treatments were: regarding the height, 75% LC + 25% SC, 50% LC + 50% SC and 25% LC + 75% SC; the stem diameter, 75% LC + 25% SC and 50% LC + 50% SC; and the nutritional assessment, 75% LC + 25% SC. To produce T. granulosa seedlings, it is recommended the use of a combination of sewage sludge and commercial substrate.
Diferentes Misturas de Substratos com Lodo de Esgoto Compostado Enriquecido e Substrato Comercial em Quaresmeira
Keywords: Mineral plant nutrition; Reforestation; Seedbed; Tibluchina granulosa